2000
DOI: 10.1080/001731300300045300
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measures of spores of Alternaria and pollen concentrations in air over two towns in rural Australia

Abstract: Mitakakis, TZ. & McGee, PA. 2000. Reliability of measures of spores of Alternaria and pollen concentrations in air over two towns in rural Australia. Multiple sites for Burkard sampling. ± Grana 39: 141± 145. ISSN 0017-3134 .We examined the reliability of measurements from a single Burkard volumetric trap to represent the distribution of airborne concentrations of spores of Alternaria and pollen across two towns in rural Australia. Each town was sampled with three traps, sited 2.0 to 4.9 km apart, simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Hundreds of conidia from Alternaria spp. have been found per m 3 of air sampled 15 m above ground in Europe, (Angulo-Romero et al 1999), USA (Dixit et al 2000) and Australia (Mitakakis and McGee 2000). However, for Puccinia recondita it was shown that the general directions of air mass movement prevented exchange of races between the European and Asian parts of Russia (Pavlova and Mikhailova 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of conidia from Alternaria spp. have been found per m 3 of air sampled 15 m above ground in Europe, (Angulo-Romero et al 1999), USA (Dixit et al 2000) and Australia (Mitakakis and McGee 2000). However, for Puccinia recondita it was shown that the general directions of air mass movement prevented exchange of races between the European and Asian parts of Russia (Pavlova and Mikhailova 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Urban environments are widely studied while rural areas remain far less studied. The latter environment is of particular interest (Mitakakis and McGee 2000) because large amounts of spores are released from crops. Also, only a few studies have compared spore concentrations in urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal spore concentrations are governed by the nature and distance of the major sources, prevailing meteorological conditions and local topography (Angulo, Mediavilla & Domı´nguez 1999). Rural areas are of particular interest (Mitakakis & McGee 2000), because large amounts of conidial spores are thought to be released from crops, and respiratory symptoms have been recorded coinciding with crop ripening, harvest and storage (Lacey 1971, Hill et al 1984, O'Hollaren et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Most fungal species act saprotrophically, colonising all stages of plant growth, or as plant pathogens, prompting considerable economic losses worldwide (Hjelmroos 1993, Infante et al 1997a. Fungal spores can also have a serious detrimental effect on human health, triggering respiratory diseases and allergenic processes (O'Hollaren et al 1991, Peat et al 1995, Ricci et al 1995, Mitakakis & McGee 2000.…”
Section: Introductionmentioning
confidence: 99%